2013
DOI: 10.1080/01635581.2014.847964
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Eicosapentaenoic Acid and Docosahexaenoic Acid Supplementation Reduces Bone Resorption in Postmenopausal Breast Cancer Survivors on Aromatase Inhibitors: A Pilot Study

Abstract: Postmenopausal breast cancer survivors are living longer; however, a common class of drugs, aromatase inhibitors (AI), depletes estrogen levels, promotes bone loss, and heightens fracture risk. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) may offset AI effects to bone because of the known effects on cellular processes of bone turnover. Therefore, we hypothesized that 4 g of EPA and DHA daily for 3 mo would decrease bone turnover in postmenopausal breast cancer survivors on AI therapy in a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…In line with this, research conducted by Sun et al (2003) reported the inhibitory effect of both EPA and DHA on osteoclastogenesis in bone marrow macrophages [33]. In a pilot study, Hutchins-Wiese et al (2014) showed that high-dose EPA and DHA supplementation reduced bone resorption in postmenopausal breast cancer survivors on aromatase inhibitors [34]. Increased dietary intake of AA has also been shown to lower the risk of hip fractures by 80% in men [35].…”
Section: Discussionmentioning
confidence: 90%
“…In line with this, research conducted by Sun et al (2003) reported the inhibitory effect of both EPA and DHA on osteoclastogenesis in bone marrow macrophages [33]. In a pilot study, Hutchins-Wiese et al (2014) showed that high-dose EPA and DHA supplementation reduced bone resorption in postmenopausal breast cancer survivors on aromatase inhibitors [34]. Increased dietary intake of AA has also been shown to lower the risk of hip fractures by 80% in men [35].…”
Section: Discussionmentioning
confidence: 90%
“…The test diet was higher in ω‐3 PUFA than the control diet, which at high doses have renoprotective effects in experimental canine models of kidney disease, although it is not possible from this study to assess whether the increased concentration of ω‐3 PUFA had effects on the cats’ renal function. It is also possible that this difference could have had an impact on calcium‐phosphate homeostasis as there is emerging evidence that ω‐3 PUFA supplementation might reduce bone turnover in postmenopausal women . Markers of bone turnover were not examined in this study; however, ionized calcium concentrations increased more greatly in the test diet group, which could be a result of decreased calcium deposition in bone.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to results on ω-3 LCPUFAs, we found that PLA inhibited NF-κB activity as well as the activation of the MAPKs, JNK and ERK. Supplementation with high doses of EPA and DHA has been shown to decrease bone loss associated with breast cancer [40]. Furthermore, diets rich in ω-3 LCPUFA have been associated with increased bone mineral density and peak bone mass [30].…”
Section: Discussionmentioning
confidence: 99%